Description of three new Boulenophrys species from eastern Guangdong, China, emphasizing the urgency of ecological conservation in this region (Anura, Megophryidae) - Wang, Jian; Zeng, Zhao-Chi; Lyu, Zhi-Tong; Qi, Shuo; Liu, Zu-Yao; Chen, Hong-Hui; Lu, Yu-Hong; Xiao, Hui-Wen; Lin, Can-Rong; Chen, Kai; Wang, Ying-Yong (Zootaxa, 2022)
The hilly region in eastern Guangdong, China lacks comprehensive scientific investigations for decades, especially in terms of herpetofauna. In recent years, several highly threatened amphibians have been gradually discovered from this region. In this work, three new species of the genus Boulenophrys are described, which are endemic from only one or two known localities in eastern Guangdong. These discoveries enrich the diversity of Boulenophrys in eastern Guangdong. With the large number of threatened urodeles and anuran species occurring in this densely populated area, the unique herpetological diversity in eastern Guangdong is facing the impacts of habitat degradation and fragmentation, and conservation actions are urgently required.